2006
DOI: 10.1002/pros.20326
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin receptor expression is upregulated in prostate cancer

Abstract: These findings demonstrate that PAR1 expression is increased in prostate cancer. Its predominant expression in vascular network suggests that it may play a direct and crucial role in angiogenesis and could be a relevant target for therapeutic interventions to control or to prevent disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 45 publications
4
79
0
1
Order By: Relevance
“…From the two derived cDNAs, the target gene, encoding PAR1 receptor known to be expressed and regulated in prostate carcinoma and cell lines (Kaushal et al, 2006;Yuan and Lin, 2004), was quantified, as well as two dedicated HKGs, namely TBP and PPIA. Both were chosen for their discrepant expression under variable hypoxic conditions: TBP showed one of the greatest stability in LNCaP cell line whereas PPIA was one of the less stable HKG in this model system.…”
Section: Gene Expression Varies According To the Hkg Usedmentioning
confidence: 99%
“…From the two derived cDNAs, the target gene, encoding PAR1 receptor known to be expressed and regulated in prostate carcinoma and cell lines (Kaushal et al, 2006;Yuan and Lin, 2004), was quantified, as well as two dedicated HKGs, namely TBP and PPIA. Both were chosen for their discrepant expression under variable hypoxic conditions: TBP showed one of the greatest stability in LNCaP cell line whereas PPIA was one of the less stable HKG in this model system.…”
Section: Gene Expression Varies According To the Hkg Usedmentioning
confidence: 99%
“…It has been reported that PAR-1 was expressed highly in many types of cancer, such as breast cancer (9), malignant melanoma (10), prostate cancer (11), colon cancer (12), lung cancer (13), oral squamous cell carcinoma (14), esophageal cancer (15), and renal cell carcinoma (16). Early study by Even-Ram et al (9) demonstrated that PAR-1 expression levels were correlated with degree of invasiveness in both primary breast tissue specimens and established cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that expression of PAR1 is clearly increased in advanced prostate cancer (47)(48)(49). The activation of PARs promotes proliferation, invasion, and release of angiogenic factors by cancer cells (50,51), and kallikreins are enzymes that are known to cleave this receptor with a specificity similar to thrombin (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Death-The effect of rBbKIm on the viability of DU145 and PC3 cells was analyzed by the MTT assay at different time points (24,48, and 72 h) (Fig. 1).…”
Section: Action Of Rbbkim and Sbti On Cell Viability And Cellmentioning
confidence: 99%